2014
DOI: 10.1016/j.cub.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Tcf7l2 Is Required for Left-Right Asymmetric Differentiation of Habenular Neurons

Abstract: SummaryBackgroundAlthough left-right asymmetries are common features of nervous systems, their developmental bases are largely unknown. In the zebrafish epithalamus, dorsal habenular neurons adopt medial (dHbm) and lateral (dHbl) subnuclear character at very different frequencies on the left and right sides. The left-sided parapineal promotes the elaboration of dHbl character in the left habenula, albeit by an unknown mechanism. Likewise, the genetic pathways acting within habenular neurons to control their as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 45 publications
2
72
0
Order By: Relevance
“…Ablation of the parapineal, an accessory organ to the pineal, results in right isomerization of the dHb, in which both nuclei develop symmetrically with right identity [12, 13]. Conversely, loss of canonical Wnt signaling in homozygous tcf7l2 mutants causes left isomerization of the dHb [14]. Larvae with right isomerized dHb exhibit a significant reduction in locomotor activity post-shock (Figure 3A,B), increased duration of freezing (Figure 3C), and higher cortisol levels (Figure 3D), relative to controls with normal situs ( situs solitus ).…”
Section: Resultsmentioning
confidence: 99%
“…Ablation of the parapineal, an accessory organ to the pineal, results in right isomerization of the dHb, in which both nuclei develop symmetrically with right identity [12, 13]. Conversely, loss of canonical Wnt signaling in homozygous tcf7l2 mutants causes left isomerization of the dHb [14]. Larvae with right isomerized dHb exhibit a significant reduction in locomotor activity post-shock (Figure 3A,B), increased duration of freezing (Figure 3C), and higher cortisol levels (Figure 3D), relative to controls with normal situs ( situs solitus ).…”
Section: Resultsmentioning
confidence: 99%
“…The functional specialization of habenular neurons clearly correlates with the previously characterized neuroanatomical asymmetry of the habenulae. Indeed, manipulations that result in embryos with right or left habenular isomerism lead to a loss of habenular responsiveness to light or odor, respectively (49,82). Thus, correct LR asymmetry in the dorsal habenula is crucial to segregate the processing of visual and olfactory stimuli.…”
Section: The Zebrafish Epithalamus: a Model To Link Neuronal Asymmetrmentioning
confidence: 96%
“…However, the molecular mechanisms underlying the timing of neuronal birth, its impact on habenular specification, and its link with pp function are not clear. Studies from the Wilson and, more recently, Carl labs have revealed that the acquisition of dHbl or dHbm fate requires the precise control of Wnt signaling (26,81,82) (Table 1). Indeed, genetic contexts that result in increased Wnt signaling (axin1 mutant) lead to a double right habenular phenotype (26).…”
Section: Figurementioning
confidence: 97%
“…Experiments of PpO ablation and mutant conditions that delay the onset of PpO asymmetric translocation reveal a requirement of an asymmetrically positioned PpO for the subsequent development of a sub-type of asymmetries in the Hb ( figure 4a(iii)) [40][41][42]58]. These asymmetries result from L-R differences in cell fate decisions towards two main neuronal identities, and it is possible that the PpO modulates these fate decisions as well as the timing of asymmetric habenular neurogenesis by acting on the Notch and Wnt signalling pathways [43,44].…”
Section: Nodal As Laterality Modulator In Midlineunpaired Structuresmentioning
confidence: 99%